AN OVERVIEW OF ARC MAGMA PETROGENESIS - Hartono, U.; Sulistyawan, R. Isnu H. (Jurnal Geologi dan Sumberdaya Mineral, 2011)
The petrogenesis of subducted-related magmas is complicated, and has been subject of controversy and widely discussed among petrologists, involving multi sources and multi processes. The source of arc magmas includes upper mantle with either MORB-like or OIB-like, the subducted slab which consists of an oceanic basaltic crust and possibly sediments, including material derived either through melting or release of fluid, and the arc crust. The process involves fractionation, assimilation or contamination and magma mixing. There are two types of contamination including source and crustal contaminations. Trace element and isotopic evidences suggest that most arc magmas are derived from melting of upper mantle induced by released fluids and incompatible elements from a subducted oceanic crust. Subsequent fractionation with or without assimilation or contamination and magma mixing would result in more acid magmas. However, crustal-derived magmas, resulted from melting of either subducted slab or lower crust, are also present in some arcs.Keywords : arc magmas, petrogenesis, overview